Managing the Implementation of Development Projects : A Resource Kit on CD-ROM for Instructors and Practitioners - Course Syllabus and CD-ROM - World Bank (Washington, DC, 2013)
This 12-module CD-ROM library of print-based learning materials is designed for classroom training of developing country project managers responsible for overseeing the implementation of development and other projects. Each module includes performance-based instructional objectives; module and session outlines with a timetable of activities; scripted lectures with corresponding visuals; case studies, exercises, and solution sets with teaching notes; self-assessment questions and answers; and selected readings. The resource kit provides enough information and practice to instill a solid understanding of the principles of project implementation and an awareness of good practices.